Thermo-physical properties of "Tubang Bakod" (Jatropha curcas L.) Seeds - De Vela, Roger Jay L. (Philippine agricultural mechanization journal)
The physical properties of Jatropha seeds at different moisture levels were determined using appropriate scientific procedures. Physical dimensions were measured using a dial caliper. For Jatropha seeds, length measurements ranged from 16 to 17 mm while width and thickness ranged from 11 mm to 11.3 mm and from 8.4 mm to 8.6 mm, respectively. Physical dimensions of seed samples were significantly affected by moisture content (wet basis). Jatropha kernels exhibited lower values of length (13.5 to 13.6 mm) width (7.6 to 8.2 mm) and thickness (5.9 to 6.6. cm). Moisture content affected only the width and thickness of the Jatropha kernels. Using a standard bulk density tester, bulk density of Jatropha seeds was determined to increase from 33.4 to 37.4 kg/m3 and from 36.7 to 48.1 kg/m3 for the kernels, both at moisture content range of 4 to 32 percent. In both cases, the effect of moisture content was accurately described by linear equations. True density on the other hand was measured for the fresh Jatropha samples (32 percent wet basis). The measured values were 0.767 g/cm3 and 0.755 g/cm3 for seeds and kernels, respectively. At the same moisture content range mentioned above, angle of repose increased from 21.1 to 24.9 degrees for the Jatropha seeds and from 14.90 to 23.8 degrees for the kernels. The thermal properties measured for Jatropha samples at different moisture levels were specific heat, thermal conductivity and thermal diffusivity. Specific heat was determined using the method of mixtures. The method consisted of determining the temperature change of toluene contained in the calorimeter (thermos bottle) when a known quantity of test material is mixed at a known temperature. The variation of specific heat was 0.783 to 1.072 kJ/kg-K for Jatropha seeds, 0.751 to 1.318 kJ/jg-K for kernels and 0.78 to 1.157 kJ/kg-K for the seeds' shells. The specific heat data appeared to be affected to be affected by moisture content and this effect was accurately described by certain heat capacity models. A modified Fitch apparatus was constructed to measure the thermal conductivity of Jatropha kernels. It consisted of a constant temperature vacuum flask, a copper plug and copper rod assembly. The sample was sandwiched between the copper plug and copper rod and the temperature history of the sample was recorded as heat was transferred fro the copper rod assembly to the product. The thermal conductivity increased with the increase in moisture content and varied from 0.056 to 0.170 W/m-K. Thermal conductivity data were correlated with moisture content by a linear equation. Thermal diffusivity values were calculated using the mathematical relationship among bulk density, specific heat and thermal conductivity. It is also increased with moisture content and values ranged from 2.03 x 10 -6 to 2.66 x 10 -6 m2/s. This increase of thermal diffusivity values with moisture content was described by a linear model.